Analysis of Immoral Comedy in the Film "The Dictator" - Muhammad Tiffano (Cinematology: Journal Anthology of Film and Television Studies, 2023)
"The Dictator" is a 2012 comedy film that uses immoral humor to discuss sensitive and controversial topics such as dictatorship, terrorism, and repression. The film follows the story of a dictator from a fictional Middle Eastern country who comes to the United States and experiences life as an ordinary citizen. The purpose of using amoral humor is to provoke the audience and start a discussion about politics and freedom. Amoral comedy is a genre that explores taboo and unusual topics with humor. The Dictator uses this genre to indulge ethical and moral issues related to politics and invites the audience to think about problems and hypocracy in politics. The method used in making this journal is descriptive in nature about how theory becomes the main thing in the problems that are happening. The findings of this study indicate that the concept of amoral comedy which is a part of the film “The Dictator” is considered through in-depth research. So the amoral comedy in this film conveys a message through the entire story that can provide valuable insight into the ways in which directors use humor to interact with important social and political issues. The implications of this research can be a reference for screenwriters or comedy film directors.